Lessons from the Digital Agricultural Advisory Services (DAAS) project in Ethiopia: Dairy use case - Abate, Gashaw T.; McNamara, Brian; Bonilla, Juan; Yesigat, Habtamu; Spielman, David J. (International Food Policy Research Institute, 2025)
Agricultural extension services are a cornerstone of rural development and a vital instrument for policymakers to directly shape economic, social, and environmental outcomes in rural areas. These services aim to enhance farm productivity by promoting the adoption of agricultural technologies, inputs, and management practices. Through outreach, training, knowledge sharing, and learning, extension activities help bridge the gap between research and practice, potentially supporting more resilient and productive farming systems (Davis 2008; Jack 2013).